The dog who knew too much eaudiobook - Quinn, Spencer (Chet and Bernie Mystery, 2011)
This fourth entry in the New York Times best-selling mystery series finds canine narrator Chet and his human companion Bernie-"the coolest human/pooch duo this side of Wallace and Gromit" (Kirkus Reviews)-searching for a missing child at a wilderness camp. The mother thinks the boy was snatched by his father-her ex. But Chet's sniffing sends the case in a different direction. "Great, cozy fun even if you're not nuts for dogs."-Library Journal